2022
DOI: 10.3389/fpsyg.2022.854810
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Online Intervention for ADHD: A Meta-Analysis and Systematic Review

Abstract: BackgroundWith the popularity of computers, the internet, and the global spread of COVID-19, more and more attention deficit hyperactivity disorder (ADHD) patients need timely interventions through the internet. At present, there are many online intervention schemes may help these patients. It is necessary to integrate data to analyze their effectiveness.ObjectivesOur purpose is to integrate the ADHD online interventions trials, study its treatment effect and analyze its feasibility, and provide reference info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, ADHD appears to be neglected in the evidence base of DHIs (19). In particular, there is limited evidence for interventions which provide support for young people with ADHD, aged 16-25 (17,19). This is of importance because of the transitions that young people often experience at this age, such as the transition from child to adolescent mental health services, within the education system, and leaving home/parental-care.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…However, ADHD appears to be neglected in the evidence base of DHIs (19). In particular, there is limited evidence for interventions which provide support for young people with ADHD, aged 16-25 (17,19). This is of importance because of the transitions that young people often experience at this age, such as the transition from child to adolescent mental health services, within the education system, and leaving home/parental-care.…”
Section: Rationalementioning
confidence: 99%
“…A key nding from the scoping review is that relatively few studies focus on the development of interventions for adolescents and young people with ADHD. Other systematic reviews in this area of research nd interventions aimed at younger populations, but the evidence for people aged 16-25 is limited (17,19). This was the rst review to exclusively focus on this age range, and only 10 papers were yielded.…”
Section: Outstanding Questions For Futurementioning
confidence: 99%
See 1 more Smart Citation
“…To date, only one meta-analysis has been carried out, which included six studies and found that internet-based interventions increased attention and social functioning. Still, despite some indications of benefit, the number of studies were few and included small sample sizes ( n s < 30), highlighting the need for additional research ( Shou et al, 2022 ). Apart from outcome studies, investigations on the feasibility and usability of online interventions and smartphone applications have also been made.…”
Section: Introductionmentioning
confidence: 99%
“…Given the scarcity of research on psychological treatments for ADHD-symptoms in general, and internet-based interventions in particular, there is a need for additional studies in order to test their efficacy. This is especially true for adequately powered randomized controlled trials with longer follow-up assessments ( Shou et al, 2022 ). Furthermore, given the many challenges that face individuals with ADHD-symptoms in both educational and occupational settings and the lack of support being provided in these contexts, providing online interventions may prove to be helpful for many university students and employed individuals with these types of issues.…”
Section: Introductionmentioning
confidence: 99%